Catalyst for solid polymer fuel cell and method for producing catalyst for solid polymer fuel cell

By forming a hydrophobic porous polymer barrier layer on the solid polymer type fuel cell catalyst, the problem of deterioration of activity during long-term use is solved, and the balance optimization of the durability and initial activity of the catalyst is achieved.

CN119856304APending Publication Date: 2025-04-18TANAKA KIKINZOKU KOGYO KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380064122.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-08-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The problem of deterioration in the activity of conventional solid polymer fuel cell catalysts during long-term use, especially the coarseness of catalyst particles and the dissolution and precipitation of platinum in the load-changing operating mode leads to a decrease in the effective surface area.

Method used

By forming a barrier layer composed of a hydrophobic porous polymer on the catalyst particles, the movement of the catalyst particles and the diffusion of platinum ions are hindered, thereby inhibiting the coarseness and deterioration of the catalyst particles.

Benefits of technology

It effectively inhibits the coarseness and activity deterioration of the catalyst particles, improves the durability of the catalyst, and maintains high initial activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856304A_ABST
    Figure CN119856304A_ABST
Patent Text Reader

Abstract

The present invention relates to a catalyst for a solid polymer fuel cell, in which catalyst particles containing Pt as an essential catalyst metal are supported on a carbon powder carrier. The present invention is provided with a barrier layer comprising a hydrophobic porous polymer that covers the carbon powder carrier and / or the at least one catalyst particle. As a result of the presence of the porous barrier layer, the catalyst according to the present invention has a peak of a Log differential pore volume (dV / d (logD)) in a region having a pore diameter of 50-200 nm (inclusive) in a pore distribution curve based on the Log differential pore volume distribution. The barrier layer is formed by any one porous polymer of polyvinyl acetate, polylactic acid, polymethyl methacrylate, polypropylene, polyvinyl chloride, polyethylene, polyacrylonitrile, polyvinyl alcohol, polyvinylidene fluoride, polyethyleneimine and polystyrene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst for a solid polymer fuel cell, and more particularly to a catalyst constituting a cathode (air electrode) of a solid polymer fuel cell, which has excellent initial activity and durability. Background Art

[0002] As a power source for automobiles and households, the practical application of solid polymer fuel cells is being promoted. Solid polymer fuel cells are mainly composed of a hydrogen electrode (anode) that supplies a fuel containing hydrogen, an air electrode (cathode) that supplies an oxidant gas such as oxygen and air, and a membrane / electrode assembly (Membrane Electrode Assembly: MEA) composed of various elements of a solid polymer electrolyte membrane sandwiched by these electrodes. In addition, a solid polymer fuel cell is formed by stacking two or more unit cells having a diaphragm with a gas flow path provided on the outside of each electrode.

[0003] Each electrode of solid polymer fuel cell is formed by mixing catalyst and solid polymer electrolyte (ionomer). All along, as solid polymer fuel cell catalyst, platinum catalyst (Pt catalyst) loaded with noble metal, particularly platinum (Pt) as catalyst metal is widely used. Pt as catalyst metal has high activity in promoting electrode reaction in both fuel electrode and hydrogen electrode. In addition, for the platinum catalyst in the past, in order to reduce the purpose of catalyst cost and improve catalyst activity by reducing Pt usage, the research example of alloy catalyst loaded with Pt and other transition metal alloy is also increasing. For example, it is also reported that Pt-Co catalyst (binary catalyst) with alloy of Pt and cobalt (Co) as catalyst particles, ternary alloy catalyst of other transition metals such as manganese alloyed on the basis of cobalt.

[0004] Through the research on the catalyst metal constituting the catalyst particles as described above, it can be said that the catalyst activity (initial activity) of the catalyst for solid polymer fuel cells has been improved. As a result, the durability of the catalyst has been required to be improved, and it has become important to suppress the activity degradation of the catalyst when the solid polymer fuel cell is driven for a long time.

[0005] In this regard, many devices using solid polymer fuel cells operate in a mode that causes load fluctuations on the catalyst. For example, in solid polymer fuel cells used as a power source for automobiles, in addition to repeated start / stop of the automobile, load fluctuations are also experienced when idling and driving, and the catalyst is subjected to load fluctuation potential cycles that cycle between low potential and high potential. Catalyst activity degradation tends to be accelerated in such a load fluctuation operation mode.

[0006] As a direct main cause of catalyst degradation, the reduction in effective surface area (sometimes also referred to as electrochemical surface area (ECSA)) caused by the coarsening of catalyst particles can be cited. In addition, as one of the main causes of the coarsening of catalyst particles, the movement of catalyst particles (platinum) under the above-mentioned load fluctuation and their aggregation can be cited. In addition, in the above-mentioned load fluctuation potential cycle, it was observed that platinum dissolved under high potential load precipitated under low potential load. In particular, solid polymer electrolyte membranes are generally strong acidic resin membranes having sulfonic acid groups, etc., and their solubility becomes higher due to water generated by fuel cell reactions. In addition, the catalyst particles are coarsened due to the platinum precipitated near the catalyst particles.

[0007] In addition, when the above-mentioned platinum is dissolved, platinum ions sometimes diffuse to the interface between the cathode and the solid polymer electrolyte membrane. At this time, the platinum ions are reduced by hydrogen leaked from the anode via the polymer solid electrolyte membrane, and a platinum belt in which platinum particles are arranged in a band is formed at the above-mentioned interface. The formation of this platinum belt becomes the main reason for the reduction of the amount of platinum in the catalyst electrode, which also becomes the main reason for the deterioration caused by the reduction of the effective surface area. The above-mentioned mechanism of the deterioration of the platinum catalyst is also observed in the platinum catalyst alloyed with other transition metals, and the dissolution and precipitation of the transition metals together with the platinum cause the deterioration caused by the coarsening of the catalyst particles and the reduction of the effective surface area.

[0008] As a solution to improve the durability of solid polymer fuel cell catalysts using platinum or platinum alloys as catalyst particles, the applicant of the present application has proposed several countermeasures. For example, a catalyst having a water-repellent layer and a predetermined fluorine compound loaded on the catalyst is disclosed (Patent Document 3). In this catalyst, the water generated by the fuel cell reaction is rapidly discharged by the water-repellent layer, and the dissolution of the catalyst metal sandwiched by water is suppressed, thereby ensuring durability. In addition, the platinum catalyst is subjected to a high-temperature heat treatment of more than 1000°C, the particle size of the catalyst particles is adjusted, and the valence of the platinum present on the surface of the catalyst particles is optimized (Patent Document 4). In addition, the particle size distribution of the catalyst particles is adjusted, and the proportion of catalyst particles with a small particle size is reduced (Patent Document 5).

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-27364

[0012] Patent Document 2: Japanese Patent No. 5152942

[0013] Patent Document 3: Japanese Patent No. 6053223

[0014] Patent Document 4: International Publication No. WO2018 / 194007

[0015] Patent Document 5: International Publication No. WO2019 / 065443 Summary of the invention

[0016] Problems to be solved by the invention

[0017] However, when solid polymer fuel cells are practical and popularized in the future, it is difficult to say that the above-mentioned catalysts with improved durability can fully meet their requirements. The catalyst with a water-repellent layer formed by a fluorine compound in the above-mentioned patent document 3 is insufficient in the inhibitory effect of activity reduction. In addition, although the catalysts with the particle size of the catalyst particles, the adjustment of the particle size distribution, and the adjustment of the valence of platinum as shown in patent documents 4 and 5 are better than the platinum catalysts so far in terms of activity maintenance after a long time, they have slightly poor initial activity. It is also difficult to say that the response to sacrifice some initial activity in order to improve such durability is a necessary and sufficient countermeasure.

[0018] The present invention has been made under the above background, and aims to provide a catalyst for a polymer electrolyte fuel cell using Pt as an essential catalyst metal, which has an appropriate initial activity and further improved durability.

[0019] Methods used to solve problems

[0020] The present invention for solving the above-mentioned problems is a catalyst for a solid polymer fuel cell, which is a solid polymer fuel cell catalyst obtained by loading catalyst particles containing Pt as an essential catalyst metal onto a carbon powder carrier, and is characterized in that it has a barrier layer composed of a hydrophobic porous polymer and coating the above-mentioned carbon powder carrier and / or at least one of the above-mentioned catalyst particles.

[0021] If the main reason for the degradation of the activity of the solid polymer fuel cell catalyst is the coarsening caused by the movement of catalyst particles, dissolution of platinum, etc., and precipitation, then as a means of suppressing degradation, there can be cited a partition that hinders the movement of catalyst particles and sets diffusion of platinum ions, etc. generated by dissolution. In the solid polymer fuel cell catalyst of the present invention, a barrier layer having these functions is used to coat the carrier and / or catalyst particles.

[0022] Regarding the mechanism of suppressing activity degradation by the barrier layer of the solid polymer fuel cell catalyst of the present invention, the following is used: Figure 1 (a) and (b) are described. As described above, in the existing solid polymer fuel cell catalyst ( Figure 1 In (a), the catalyst particles migrate and aggregate with surrounding catalyst particles, causing the catalyst particles to become coarse. Figure 1 (a)(i)) and coarsening of other catalyst particles due to precipitation of metal ions generated by dissolution of the catalyst metal near other catalyst particles ( Figure 1 (a)(ii)), and thus the activity may be deteriorated. In contrast, in the catalyst of the present invention ( Figure 1 (b)) The barrier layer covering the catalyst particles captures the catalyst particles or the barrier layer covering the surface of the carrier blocks the movement of the catalyst particles, thereby suppressing the aggregation and coarsening of the surrounding catalyst particles. Figure 1 (b)(i)). In addition, even if dissolution occurs in the catalyst particles covered by the barrier layer, the barrier layer blocks platinum ions and inhibits diffusion out of the range. This can reduce precipitation near other catalyst particles ( Figure 1 (b)(ii)). In addition to the effect of inhibiting the coarsening of these catalyst particles, the barrier layer can also prevent the diffusion of platinum ions into the solid electrolyte membrane and inhibit the formation of platinum bands at the interface between the cathode and the solid polymer electrolyte membrane. Inhibition of the formation of platinum bands can prevent the reduction of the effective surface area caused by the reduction of the catalyst metal component, which helps to inhibit the reduction of activity.

[0023] However, regarding the structure of the barrier layer, if it is a film-like film that blocks the catalyst particles from the outside, the activity (initial activity) of the catalyst is reduced. In order to carry out the electrode reaction, it is indispensable to supply the reaction gas (oxygen) to the surface of the catalyst particles, and it is also necessary to release water molecules as reaction products from the vicinity of the catalyst particles. The barrier layer requires such permeability to the reaction gas and water molecules. In the present invention, the barrier layer is made to have a porous structure composed of a hydrophobic polymer, which imparts permeability to the reaction gas, etc., and ensures the activity of the catalyst. On the other hand, by making the barrier layer a hydrophobic polymer, water containing dissolved platinum ions, etc. is difficult to release from the barrier layer, thereby inhibiting the diffusion of platinum ions, etc. Below, the structure and manufacturing method of the solid polymer fuel cell catalyst of the present invention having the above-mentioned degradation inhibition mechanism are described in detail.

[0024] (A) Structure of the catalyst for solid polymer fuel cell of the present invention

[0025] As described above, the catalyst for solid polymer fuel cells of the present invention is characterized in that a barrier layer is formed on a catalyst using platinum or a platinum alloy as catalyst particles. In addition, as for the catalyst to which the barrier layer is applied, an existing catalyst for solid polymer fuel cells can be used as an object. In the following description, a catalyst for solid polymer fuel cells suitable as an object of the present invention is described, and on this basis, the composition and characteristics of the barrier layer are described.

[0026] (i) Catalyst particles

[0027] The catalyst particles of the solid polymer fuel cell catalyst of the present invention have Pt as an essential constituent metal, and have no other essential conditions in composition or structure. The fact that Pt is an essential catalyst metal is based on the fact that Pt has high activity, especially high initial activity. In the solid polymer fuel cell catalyst of the present invention, as catalyst particles, in addition to catalyst particles composed of Pt, catalyst particles composed of Pt alloys formed by alloying other metals M with Pt are also used.

[0028] When using catalyst particles composed of Pt alloy, the metal M alloyed with Pt can be at least one of Co, Ni, Mn, Fe, Ti, Zr, and Sn. By alloying these metals, the amount of Pt used as the catalyst metal can be reduced, and a highly active catalyst can be prepared. Regarding Pt alloys, specifically, binary Pt alloys such as Pt-Co alloys and Pt-Ni alloys; ternary Pt alloys such as Pt-Co-Mn alloys, Pt-Co-Zr alloys, and Pt-Co-Ni alloys can be listed.

[0029] For the alloy composition when applying the catalyst particles composed of Pt alloy, the composition of the prior art can also be applied. For example, in the Pt-Co alloy catalyst of the binary alloy, the composition of Pt:Co=1:0.14~0.67 in terms of molar ratio is preferred. In addition, in the Pt-Co-Mn alloy catalyst of the ternary alloy, the molar ratio of Pt:Co:Mn=1:0.25~0.28:0.07~0.10 is preferred, and Pt:Co:Mn=1:0.26~0.27:0.08~0.09 is more preferred. Similarly, in the Pt-Co-Zr alloy catalyst of the ternary alloy, the molar ratio of Pt:Co:Zr=3:0.5~1.5:0.1~3.0 is preferred, and Pt:Co:Zr=3:0.5~1.5:0.2~1.8 is more preferred. These ternary alloy catalysts are catalysts that exhibit higher initial activity than Pt-Co catalysts by adding Mn and Zr to Pt-Co catalysts. However, excessive addition of Mn and Co decreases the activity, so the above range is an appropriate range.

[0030] The particle size of the catalyst particles is preferably an average particle size of 2 to 10 nm. This is because if the particle size is smaller than 2 nm, the activity continuity characteristics cannot be clearly obtained over a long period of time, and if the particle size is larger than 10 nm, the initial activity of the catalyst cannot be sufficiently obtained.

[0031] The average particle size of the catalyst particles can be obtained, for example, by measuring the particle sizes of two or more catalyst particles based on an image obtained using an electron microscope such as a TEM, thereby calculating the average value. The particle size in the observed image can be measured by image analysis in addition to visual observation. It should be noted that the average particle size of the catalyst particles is preferably measured by arbitrarily selecting 100 or more catalyst particles.

[0032] (ii) Carbon powder carrier

[0033] For the carbon powder carrier supporting the above catalyst particles, it is preferred to use a carbon powder carrier having a specific surface area of ​​150 m 2 / g and above and 2000m 2 / g or less carbon powder. By setting it to 150m 2 / g or more can increase the area to which the catalyst is attached, so that the catalyst particles can be dispersed in a high state and the effective surface area can be increased. On the other hand, a particle size greater than 2000 m 2 When the surface area of ​​the carbon powder carrier is 250 m / g, the proportion of ultrafine pores (less than about 20 Å) that are difficult for the ion exchange resin to penetrate when forming an electrode becomes high, and the utilization efficiency of the catalyst particles becomes low. The specific surface area of ​​the carbon powder carrier is more preferably 250 m 2 / g and above 1200m 2 / g or less.

[0034] Moreover, for the catalyst of the present invention, considering the performance as an electrode of a solid polymer fuel cell, it is preferred that the loading density of the catalyst particles be set to 30 to 70%. The loading density here refers to the ratio of the mass of the catalyst particles loaded on the carrier (the total mass of the loaded platinum and metal M) to the mass of the entire catalyst.

[0035] (iii) Barrier layer

[0036] The barrier layer is a layer used to inhibit the coarsening of catalyst particles and the degradation of activity by hindering the movement of catalyst particles and hindering the diffusion of metal ions generated when the catalyst particles are dissolved. The barrier layer is formed in a manner of coating the carrier and / or catalyst particles. The barrier layer can cover the catalyst on the entire surface, but it can also be distributed in a dot-like or island-like manner on the catalyst surface and partially cover the catalyst. In addition, the barrier layer only needs to cover at least one catalyst particle, and can also cover two or more catalyst particles.

[0037] The barrier layer is composed of a hydrophobic porous polymer. A hydrophobic polymer refers to a polymer having a low affinity for water, being difficult to dissolve or be mixed in water. As a specific example of a hydrophobic polymer constituting the barrier layer, polyvinyl acetate (PVAC), polyvinyl propionate (PVPR), polylactic acid (PLA), polymethyl methacrylate (PMMA), polyethyl methacrylate (PEMA), polymethyl acrylate (PMA), polyethyl acrylate (PEA), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyethyleneimine (PEI), and polystyrene (PS) can be cited. As described later, the barrier layer of the present invention is formed by temporarily dissolving a hydrophobic polymer in an organic solvent such as alcohol and then precipitating on a catalyst. Therefore, a polymer soluble in an organic solvent is preferably used. In addition, as a solvent for forming a barrier layer, a mixed solvent of a hydrophilic organic solvent and water is sometimes used. As a polymer capable of efficiently forming a porous polymer layer while considering the solubility of these solvents, a polymer having an ester bond in the structure of the monomer is preferably used. Specifically, more preferred hydrophobic polymers include PVAC, PVPR, PLA, PMMA, PEMA, PMA, and PEA.

[0038] The barrier layer is a hydrophobic polymer and has a porous structure for ensuring permeability of reaction gas necessary for fuel cell reaction. The barrier layer having the porous structure has pores with a pore diameter of 50 nm or more and 200 nm or less.

[0039] The pores with a pore diameter of 50 nm or more and 200 nm or less are pores that are not contained in a conventional catalyst using carbon powder as a carrier. Therefore, the pores of the barrier layer have a clear influence on the overall pore distribution of the catalyst. Specifically, the catalyst of the present invention shows a peak from the barrier layer in the region where the pore diameter is 50 nm or more and 200 nm or less in the pore distribution curve based on the Log differential pore volume distribution. The Log differential pore volume represents the relationship between the size of the pores of the catalyst and its volume, and is the value (dV / d(logD)) obtained by dividing the differential pore volume dV of the increased part of the pore volume between the measurement points as the pore diameter by the logarithmic difference value d(logD) of the pore diameter. The Log differential pore volume distribution is a distribution curve obtained by plotting the Log differential pore volume value relative to the average pore diameter of each interval. It should be noted that in the determination of the pore distribution of the catalyst, a general gas adsorption method can be applied, and nitrogen (N2) is preferably used as the adsorbed gas at this time.

[0040] In the present invention, showing a peak in the region where the pore diameter is greater than 50 nm and less than 200 nm means that in the above-mentioned pore distribution curve, a peak containing the maximum value of the Log differential pore volume (dV / d(logD)) is shown in the region where the pore diameter is greater than 50 nm and less than 200 nm. Moreover, in the catalyst of the present invention, it is preferred that the height of the peak in the region where the pore diameter is greater than 50 nm and less than 200 nm is greater than 1.0. A catalyst in which the height of the peak in the region where the pore diameter is greater than 50 nm and less than 200 nm is less than 1.0 is substantially the same as a catalyst without a barrier layer, and the effect produced by the barrier layer cannot be expected. It should be noted that the upper limit of the height of the peak in the region where the pore diameter is greater than 50 nm and less than 200 nm is preferably set to less than 3.0. It should be noted that in the catalyst of the present invention, an increase in the Log differential pore volume value from the pores of the carbon fine powder as a carrier is sometimes observed. However, the appearance of a small peak in the pore distribution curve is not essential to the present invention, and depending on the type of carbon powder, a peak of the Log differential pore volume value may appear only in the region of pore diameters of 50 nm to 200 nm.

[0041] The presence or absence of a barrier layer in the catalyst of the present invention, that is, the presence of a polymer on the catalyst surface, and its chemical structure can be analyzed by TOF-SIMS (time-of-flight secondary ion mass spectrometry). TOF-SIMS is a method for mass separation of ions (secondary ions) released from the sample surface when the sample is irradiated with an ion beam (primary ions) using their flight time difference. At this time, the flight time of the secondary ions is proportional to the square root of the weight, so quantitative analysis of the metals in the sample can be performed. In addition, chemical structure information of organic matter (polymer) can also be obtained in SIMS, so it is suitable for the present invention. Moreover, in TOF-SIMS, information related to elements and molecular species present on the extreme surface of the sample (depth below 1nm) can be obtained, so the detection intensity of Pt ions also varies depending on the presence or absence of coating, and the coating using the barrier layer can also be confirmed.

[0042] In the catalyst for solid polymer fuel cells of the present invention, the barrier layer not only inhibits the coarsening of catalyst particles, but also imparts hydrophobicity to the catalyst. The improvement of the hydrophobicity also helps to inhibit the degradation of the catalyst and improve durability. One of the main reasons for the degradation of the activity of the catalyst is the dissolution of the catalyst particles (Pt), and water is sandwiched in the dissolution of the catalyst particles. By imparting hydrophobicity to the catalyst through the barrier layer, the discharge of water generated in the fuel cell reaction can be promoted, thereby reducing the dissolution of the catalyst particles.

[0043] The catalyst for solid polymer fuel cell of the present invention having the barrier layer described above has an initial activity equal to or higher than that of the catalyst without the barrier layer, but the decrease in activity caused by the increase in reaction time is suppressed, and the durability is excellent. Therefore, as a basic catalyst, by appropriately loading the catalyst particles of the above composition and particle size on a suitable carbon powder carrier, a catalyst with an excellent balance between initial activity and durability can be prepared.

[0044] (B) Method for producing catalyst for polymer electrolyte fuel cell of the present invention

[0045] Next, the method for manufacturing the catalyst for the solid polymer fuel cell of the present invention is described. The catalyst of the present invention is manufactured by treating a Pt catalyst or a Pt alloy catalyst for forming a barrier layer. At this time, as a treatment for forming a barrier layer, there is the following method: immersing the catalyst in a solution in which a polymer is dissolved, and then performing a treatment for separating the polymer from the solution, so that the polymer precipitates on the catalyst. That is, the catalyst manufacturing method of the present application is a method for manufacturing a catalyst for a solid polymer fuel cell, which includes: a step of preparing a catalyst in which catalyst particles containing Pt as an essential catalyst metal are loaded on a carbon powder carrier; a step of preparing a polymer solution in which a polymer is dissolved in an organic solvent; and after dispersing the above-mentioned catalyst in the above-mentioned polymer solution, the polymer solution is heated or cooled, or water is added, so that the above-mentioned polymer precipitates on the surface of the above-mentioned catalyst to form a barrier layer.

[0046] Regarding the process of preparing a Pt catalyst or a Pt alloy catalyst for forming a barrier layer, a catalyst for the purpose of treatment can be manufactured in advance, or a commercially available catalyst can be prepared. Regarding the manufacture of catalysts for solid polymer fuel cells, the Pt catalyst can be manufactured by appropriately loading Pt on a carbon micropowder carrier, and can be manufactured by appropriately undergoing post-treatments such as heat treatment. In addition, the Pt alloy catalyst can be manufactured by using the Pt catalyst as a precursor, loading the metal (M) to be alloyed thereon, and performing alloying heat treatment, etc.

[0047] The manufacturing method of Pt catalyst is based on the general liquid phase reduction method as a basic process. In the liquid phase reduction method, a carbon powder carrier is mixed with a Pt compound solution to manufacture a mixed solution, a reducing agent is added to the mixed solution, Pt is reduced and precipitated, and loaded onto the carbon powder carrier, thereby manufacturing a Pt catalyst. As Pt compound solution, dinitrodiammineplatinum nitric acid solution, chloroplatinic acid aqueous solution, chloroplatinic acid potassium aqueous solution, hexaammineplatinum hydroxide solution, etc. can be listed. In addition, alcohol (methanol, ethanol, etc.) can be listed as a reducing agent added to the mixed solution. Then, after adding the reducing agent, it is appropriately heated and refluxed, thereby causing the Pt particles to be loaded onto the carrier. By this reduction treatment, a Pt catalyst is obtained. In addition, it can also be used as a precursor for manufacturing a Pt alloy catalyst.

[0048] In addition, the Pt catalyst after the reduction treatment can be heat-treated as needed. For the temperature of the heat treatment, the heating temperature is set to a relatively high temperature range of more than 800°C and less than 1200°C. When it is lower than 800°C, it is difficult to become a catalyst with good durability. In addition, heat treatment exceeding 1200°C is worried about the reduction of initial activity due to the coarsening of catalyst particles. The heat treatment is preferably carried out in a non-oxidizing atmosphere such as a reducing gas atmosphere and an inactive gas atmosphere, and a reducing gas atmosphere is particularly preferred. Specifically, a hydrogen atmosphere (more than 50% hydrogen) is preferred.

[0049] The Pt alloy catalyst with Pt alloy (Pt-M alloy) as catalyst particles can be manufactured by loading metal M on the Pt catalyst of the above-mentioned manufacture and performing heat treatment for alloying. The load of metal M can also be applied to liquid phase reduction method. That is, the metal salt solution of metal M is contacted with the Pt catalyst, and reduction treatment is performed to precipitate M in a metallic state near the Pt particles. As the metal salt solution of metal M, aqueous solutions of chlorides, nitrates, acetates, and sulfates of each metal can be applied. In addition, by adjusting the loading amount of metal M, the composition of the Pt alloy that becomes the catalyst particles can be adjusted.

[0050] After the metal M is loaded on the Pt catalyst, a heat treatment is performed to alloy the Pt with the metal M. The heat treatment temperature is set to 700-1200°C. In the heat treatment below 700°C, the alloying between the metals is insufficient, resulting in a catalyst lacking activity. In addition, a heat treatment exceeding 1200°C is feared to cause the coarsening of the catalyst particles. The heat treatment is preferably carried out in a non-oxidizing atmosphere, particularly preferably in a reducing atmosphere (hydrogen atmosphere, etc.). By alloying the heat treatment, a catalyst having a Pt alloy as the catalyst particles can be obtained.

[0051] Then, in the present invention, a barrier layer is formed on the Pt catalyst or Pt alloy catalyst prepared as above. In the formation of the barrier layer, first, a solution (polymer solution) of a hydrophobic polymer forming the barrier layer is prepared. As the solvent of the polymer solution, an organic solvent is preferably used. Specifically, alcohol (ethanol, methanol, propanol, butanol, pentanol, hexanol), acetone, ethylene glycol, dimethyl sulfoxide (DMSO), 1,4-dioxane, N,N-dimethylformamide (DMF), dimethyl ether, diethyl ether, etc. are preferred. In addition, in the solvent of the polymer solution, a mixed solvent obtained by mixing a hydrophilic organic solvent such as alcohol and acetone with water can sometimes be used. In a polymer solution based on a mixed solvent, the solubility of the polymer can be adjusted by changing the mixing ratio of the organic solvent to water. Which solvent is selected can be determined according to the solubility of the polymer forming the barrier layer. For example, as a solvent when making the barrier layer PVAC, alcohol can be applied. In addition, acetone is preferred in the case of PLA, and a mixed solvent of alcohol or alcohol and water (warm water) is preferred in the case of PMMA. In the preparation of polymer solution, if the dissolution of polymer needs to be heated, it can be carried out while heating the solution at a temperature not exceeding the boiling point of the solvent. The amount of polymer contained in the polymer solution is based on the mass of the catalyst as a whole (the total mass of polymer and catalyst), preferably calculated as more than 2.5 mass % and less than 10 mass % in mass %. When the polymer amount is excessively increased, the performance is reduced due to the obstruction of gas diffusion and the increase of resistance. In addition, when it is less than 2.5 mass %, it is difficult to form an effective barrier layer. It should be noted that the polymer solution is as long as the amount of liquid that the catalyst prepared as the object of treatment can be immersed is more than.

[0052] Next, a catalyst (Pt catalyst or Pt alloy catalyst) as a treatment object is immersed in the polymer solution and mixed to prepare a slurry. At this time, in the manufacture of the slurry, the polymer solution and the catalyst can be put into it together, or the catalyst can be dispersed in a solvent in advance and the polymer solution can be added thereto. In addition, the slurry can be stirred and heated as needed during mixing.

[0053] Then, the polymer in the slurry is precipitated to form a barrier layer on the catalyst surface. For the operation of polymer precipitation, the operation of heating or cooling the slurry manufactured above, or adding water can be listed. The precipitation operation is selected according to the type of polymer. For example, PVAC and PLA produce polymer precipitation by adding more than 10 volume % of water relative to the total amount of the slurry to the slurry. In addition, there is also a polymer that is precipitated by cooling the slurry from a state maintained at a high temperature (above 50°C) to a low temperature (below 40°C). Through these operations, a barrier layer is formed by precipitating the polymer. After the barrier layer is formed, the catalyst is extracted from the slurry by filtration and appropriately washed, thereby obtaining the catalyst of the present invention.

[0054] Effects of the Invention

[0055] As described above, the present invention provides a polymer electrolyte fuel cell catalyst having particularly excellent durability compared to conventional polymer electrolyte fuel cell catalysts that support catalyst particles containing Pt. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a conceptual diagram for explaining the degradation mechanism of a polymer electrolyte fuel cell catalyst and the inhibitory effect of a barrier layer.

[0057] Figure 2 This is a pore distribution curve of the catalyst for a solid polymer fuel cell produced in the first embodiment (barrier layer: PVAC).

[0058] Figure 3 These are water vapor adsorption isotherms of the catalyst of the first embodiment and the solid polymer fuel cell catalyst of the comparative example.

[0059] Figure 4 These are SEM images and cross-sectional reflection electron images of MEAs produced in the first embodiment (PVAC 5 mass %) and the comparative example.

[0060] Figure 5 These are the results of EPMA line analysis of the MEA cross sections produced in the first embodiment (PVAC 5 mass %) and the comparative example.

[0061] Figure 6 It is the particle size distribution of the catalyst particles before and after the degradation of the catalyst particles of the catalysts of the first embodiment (PVAC 5 mass %) and the comparative example. DETAILED DESCRIPTION

[0062] First embodiment :The preferred embodiment of the present invention is described below. In this embodiment, a Pt catalyst is manufactured, and a porous polymer layer composed of PVAC is formed on the Pt catalyst as a barrier layer to prepare a catalyst for a solid polymer fuel cell. Then, an MEA and a fuel cell (single cell) using the catalyst as a cathode electrode are manufactured, and their initial activity and durability are evaluated.

[0063] [Manufacturing of Pt Catalyst]

[0064] 996.42 mL of dinitrodiammine platinum nitric acid solution (Pt content: 50.00 g) and 3793 mL of pure water were placed in a production container. Then, carbon fine powder (specific surface area 800 m2) as a carrier was added while the mixture was pulverized. 2 / g, trade name: KB) 50.00g. Then, add 540mL (10.8 volume %) of modified alcohol (95% ethanol + 5% methanol) as a reducing agent and mix. The mixed solution is refluxed at about 95°C for 6 hours to reduce Pt. Then, filter, wash, and dry (60°C for 15 hours). Thus, a Pt catalyst with a loading density of 50% and an average particle size of catalyst particles of 2nm is obtained.

[0065] [Formation of barrier layer]

[0066] The barrier layer was formed on 20 g of the Pt catalyst produced above. As a polymer forming the barrier layer, powdered PVAC (product name: polyvinyl acetate, vendor: Aldrich) was dissolved in ethanol to prepare a polymer solution. In this embodiment, based on the mass of the entire catalyst (the total mass of the catalyst and the polymer), PVAC was dissolved in ethanol (300 mL) as a solvent to prepare 4 polymer solutions in such a manner as to become 2.5 mass % (0.5 g), 5 mass % (1.1 g), 7.5 mass % (1.6 g), and 10 mass % (2.2 g).

[0067] Then, under a nitrogen purge environment, a Pt catalyst is mixed in the polymer solution to prepare a slurry. At this time, the slurry is heated to near the boiling point (77°C) and maintained at near 77°C. Then, the slurry is stirred for 1 hour, and then 300 mL of water is added dropwise (5 mL / min) to precipitate PVAC to form a barrier layer. Then, the solution is filtered to separate the catalyst having the barrier layer, and the solution is washed with pure water (2L) (60°C, 30 minutes), and dried (60°C, 15 hours), thereby manufacturing the catalyst for solid polymer fuel cells of this embodiment (Examples 1 to 4).

[0068] Comparative Example 1 (Pt catalyst) As a catalyst for comparison with the present embodiment, the barrier layer was not formed on the Pt catalyst produced as described above, and it was used as a catalyst for a polymer electrolyte fuel cell as a comparative example.

[0069] [Measurement of pore size distribution]

[0070] The pore distribution was measured for the solid polymer fuel cell catalyst (PVAC / Pt-C: PVAC loading 2.5 mass%, 5 mass%, 7.5 mass%, 10 mass%) manufactured in this embodiment. In the pore distribution measurement, a specific surface area / pore distribution measuring device (model: BELSORP-miniII, manufactured by Maiqikebaier) was used as a test device. As the measurement conditions, vacuum degassing was performed at 120°C for 8 hours, and then at an adsorption temperature of 77K, the adsorption was set to nitrogen, and the adsorption-desorption isotherm was measured by a constant volume method. For the measurement results, a pore distribution curve was prepared by plotting the Log differential pore volume (dV / d(logD)).

[0071] exist Figure 2 The pore distribution curves of the solid polymer fuel cell catalysts (PVAC / Pt-C: PVAC loading 2.5 mass%, 5 mass%, 7.5 mass%, 10 mass%) of Examples 1 to 4 manufactured in this embodiment are shown in FIG. Figure 2 In the catalysts for solid polymer fuel cells of Examples 1 to 4, a peak containing the maximum value of the Log differential pore volume (dV / d(logD)) was observed in the region where the pore diameter was greater than 50 nm and less than 200 nm. In these examples, the height of the peak (dV / d(logD)) was greater than 1.0 in the region where the pore diameter was greater than 50 nm and less than 200 nm. On the other hand, for the Pt catalyst without a barrier layer of Comparative Example 1, no peak with a height greater than 1.0 was observed in the region where the pore diameter was greater than 50 nm and less than 200 nm. From these comparison results, it is believed that the barrier layer (PVAC) of the present invention has pores with a pore diameter of greater than 50 nm and less than 200 nm. Moreover, in Examples 1 to 4, when the PVAC content in the polymer solution used to form the barrier layer increases, the height of the peak in the region where the pore diameter is greater than 50 nm and less than 200 nm generally tends to increase.

[0072] It should be noted that in Examples 1 to 4 and Comparative Example 1, a peak was also observed near a pore diameter of 4 nm. This is from the pores possessed by the carbon fine powder carrier. In Comparative Example 1, although the presence of pores was counted in the region of 50 nm or more and 200 nm or less, it is believed that this is caused by the gaps between the carbon powder particles, not the pores.

[0073] [Study on the state of barrier layer]

[0074] In addition, in the present embodiment, in order to confirm the state of the barrier layer, TOF-SIMS analysis of the catalyst is performed. The analysis device used in the analysis (model: TOF-SIMS-5-200, manufactured by ION-TOF), as the analysis condition, is measured under vacuum in high mass resolution mode. In the analysis results, the counts of metal ions and ions (fragment ions) arising from organic binding groups are obtained. Then, for the obtained spectrum, the counts of each component relative to the total count are calculated, and the counts of the main components are compared in the comparative example and the present embodiment. Regarding the analysis results, the results of the catalyst of Example 2 in which a barrier layer is formed by adding 5% by mass PVAC and the catalyst without a barrier layer (Comparative Example 1) are shown in Table 1.

[0075]

[0076] According to Table 1, for the catalyst of Example 2 formed with a barrier layer, the number of counts of Pt is reduced relative to the catalyst of the comparative example without a barrier layer. In addition, for the catalyst of Example 2 formed with a barrier layer, an increase in the number of counts of organic binding groups (C2H3O2, C4H6O2) was observed, which correspond to the organic binding groups of PVAC. In TOF-SIMS analysis, the state of the analysis object can be analyzed at a depth of about 1 nm. It can be confirmed that in the catalyst of Example 2, PVAC as a barrier layer exists, and the barrier layer covers at least a portion of the catalyst particles (Pt).

[0077] [Evaluation of Hydrophobicity of Catalyst]

[0078] In addition, in order to study the hydrophobicity of the catalyst, the water vapor adsorption amount of the catalysts of Examples 2, 3, 4 (PVAC 5 mass%, 7.5 mass%, 10 mass%) and Comparative Example 1 (no barrier layer) was measured. In the determination of the water vapor adsorption amount, as an analysis device, model: BELSORP-aqua3, manufactured by Maiqikebaier, was used. As a pretreatment before analysis, the catalyst was heated at 100°C for 8 hours to dry it. The analysis condition was set to a measurement temperature of 25°C.

[0079] Figure 3 The water vapor adsorption isotherms of the catalysts of Examples 2, 3, 4 and Comparative Example 1 are shown. Figure 3 It can be seen that the catalysts of each example with a barrier layer of PVAC have a reduced amount of water vapor adsorption compared to the catalyst of Comparative Example 1 without a barrier layer. The magnitude of this reduction increases as the content of PVAC in the polymer solution increases. This confirms that the hydrophobicity of the catalyst is improved by forming a barrier layer.

[0080] [Evaluation of initial activity and durability]

[0081] Then, the initial activity and durability evaluation test of the solid polymer fuel cell catalysts of Examples 1 to 4 and Comparative Example 1 was carried out. The performance test was carried out by measuring the mass activity. In the experiment, a single cell was used to make a proton conductive polymer electrolyte membrane with an electrode area of ​​5cm×5cm=25cm 2 The MEA sandwiched between the cathode and anode electrodes was evaluated (utilization efficiency was set to 40%). As a pretreatment, a current / voltage curve was drawn under the conditions of hydrogen flow rate 1L / min, oxygen flow rate 1L / min, battery temperature = 80°C, anode humidification temperature = 90°C, and cathode humidification temperature = 30°C. Then, as a formal measurement, the mass activity was measured. For the test method, the current value (A) at 0.9V was measured, and the current value per 1gPt (A / g-Pt) was calculated from the weight of Pt coated on the electrode, and the mass activity was calculated and used as the initial activity.

[0082] Next, the MEA after the above initial activity test was subjected to a potential cycle test to evaluate durability. In the potential cycle test, pretreatment was performed by scanning between 650-1050mV at a scanning rate of 40mV / s for 20 hours (3600 cycles). Then, a formal treatment was performed by scanning between 650-1050mV at a scanning rate of 100mV / s. The formal treatment was performed for 24 hours (10800 cycles), and further scanned for 24 hours (10800 cycles) to degrade the catalyst. The mass activity of the degraded catalyst (after a total of 25200 cycles in pretreatment to formal treatment) was measured.

[0083] Table 2 shows the above-mentioned characteristics evaluation, initial activity test, and durability test results.

[0084]

[0085] As can be seen from Table 2, the maintenance rate of the activity of the solid polymer fuel cell catalyst after the degradation test of the present embodiment is higher than that of the comparative example. It is thus confirmed that by forming a barrier layer, the activity degradation of the catalyst is suppressed and the durability is improved. In addition, from the perspective of initial activity, the catalyst formed with a barrier layer as in the present invention can be said to be equal to or higher than the Pt catalyst (comparative example) without a barrier layer.

[0086] [Confirmation of the Presence of Platinum Band Formation after Durability Test]

[0087] Next, the presence or absence of platinum band formation after degradation was investigated for the fuel cell (MEA) used in the above durability test. In this study, the degraded MEA was cut with an Ar ion beam, and the cross-section of the anode catalyst layer / polymer solid electrolyte membrane / cathode catalyst was observed and analyzed using SEM and EPMA.

[0088] Figure 4 It is a cross-sectional SEM image and a cross-sectional reflection electron image of the MEA using the catalyst of Example 2 (PVAC5 mass %) and Comparative Example 1. When referring to the cross-sectional SEM, in Comparative Example 1, coarse particles of about 100 nm were observed at the interface between the electrolyte membrane and the cathode catalyst layer, which are considered to be Pt particles. The Pt particles were also observed inside the electrolyte membrane. On the other hand, in Example 2, a small amount of Pt particles were also observed at the interface, but there were no Pt particles inside the electrolyte membrane. In this regard, when observing the cross-sectional reflection electron image, in Comparative Example 1, the brightness of the Pt particles at the interface became higher, and the increase in the brightness was also observed inside the electrolyte. In addition, in Comparative Example 1, the brightness of Pt in the catalyst layer decreased. In contrast, in Example 2, the brightness of the Pt particles at the interface was low, and the brightness of Pt in the catalyst layer was high. It can be seen from this that in the catalyst layer of Comparative Example 1 using a Pt catalyst without a barrier layer, due to the dissolution of Pt, Pt ions diffuse and precipitate in the direction of the electrolyte, and the Pt particles in the catalyst layer are reduced. Furthermore, it was confirmed that in Example 2, by forming a barrier layer on the Pt catalyst, the movement and reduction of Pt from the catalyst can be suppressed.

[0089] Figure 5 The results of EPMA analysis (line analysis) of the cross-section of the MEA of Example 2 (PVAC5 mass %) and Comparative Example 1 are shown. In the MEA of Comparative Example 1, it can be clearly confirmed that a platinum band is formed at the interface between the catalyst layer and the electrolyte. In contrast, no platinum band is formed in the MEA of Example 2. From the results of the above SEM observation, it can be confirmed that by forming a barrier layer on the catalyst, the movement of Pt ions to the electrolyte membrane when platinum is dissolved can be hindered, and the formation of the platinum band can be suppressed.

[0090] In addition, the particle size distribution of the Pt particles as catalyst particles was compared for the Pt catalysts of Example 2 (PVAC5 mass %) and Comparative Example 1 after the degradation test. The particle size of the Pt particles was measured by randomly measuring 300 platinum particles from a plurality of images taken using a transmission electron microscope (TEM). Then, the particle size distribution for the measured particle size is shown in Figure 6It can be confirmed that the particle size increase after degradation of the Pt catalyst in Comparative Example 1 is large. On the other hand, it can be confirmed that in Example 2 in which the barrier layer is formed, the particle size increase is suppressed and the distribution width is narrower than that in Comparative Example 1. From this result, it can be seen that the coarsening of the Pt particles is suppressed by forming the barrier layer.

[0091] The above research results on MEA and catalyst after degradation test confirm that by forming a barrier layer on the catalyst surface as in the solid polymer fuel cell catalyst of the present embodiment, it is possible to suppress the diffusion of Pt ions toward the electrolyte membrane when the catalyst particles (Pt particles) are dissolved, the formation of platinum bands caused by precipitation, the diffusion to the vicinity of other catalyst particles, and the coarsening caused by precipitation. And it is confirmed that, through these effects, the solid polymer fuel cell catalyst of the present embodiment has a high maintenance rate of activity in the degradation test and excellent durability. And it is confirmed that the initial activity of the solid polymer fuel cell catalyst of the present embodiment is also equal to or higher than that of the Pt catalyst to date.

[0092] Second embodiment In this embodiment, a barrier layer composed of PVAC is formed on a platinum alloy catalyst (PtCo catalyst) carrying PtCo as catalyst particles to produce a catalyst for a polymer electrolyte fuel cell. The initial activity and durability of the catalyst are then evaluated.

[0093] [Manufacturing of PtCo Catalyst]

[0094] Co is loaded on the Pt catalyst manufactured in the first embodiment and alloyed to manufacture a PtCo catalyst. A metal salt solution in which 38g of cobalt chloride hexahydrate (CoCl2·6H2O) as a cobalt salt solution is dissolved in 500mL of water is made, and 100g of the Pt catalyst identical to the first embodiment is impregnated and mixed therein. Then, 2.5L of a sodium borohydride solution having a concentration of 1% by mass is added dropwise to the solution, stirred, and subjected to a reduction treatment to load cobalt on the Pt catalyst. Then, filtering, washing, and drying are performed. Then, a heat treatment for alloying is performed. Regarding the heat treatment, the heat treatment temperature is set to 1000°C in 100% hydrogen, and a heat treatment is performed for 0.5 hours to obtain a PtCo catalyst.

[0095] [Formation of barrier layer]

[0096] A barrier layer is formed on the PtCo catalyst manufactured as described above. Powdered PVAC is dissolved in ethanol to prepare a polymer solution as in the first embodiment, and a PtCo catalyst (20 g) is mixed therein to prepare a slurry. In this embodiment, the PVAC content in the polymer solution is adjusted to 5% by mass based on the mass of the entire catalyst. Then, the slurry is treated with water as in the first embodiment to precipitate PVAC and form a barrier layer. Then, the solid polymer fuel cell catalyst of this embodiment is manufactured by filtering, washing, and drying (Example 5).

[0097] Comparative Example 2 (PtCo Catalyst) As a catalyst for comparison with the present embodiment, the PtCo catalyst produced as described above was used as a catalyst for a polymer electrolyte fuel cell as Comparative Example 2 without forming a barrier layer.

[0098] [Evaluation of initial activity and durability]

[0099] For the PtCo catalysts of Example 5 and Comparative Example 2 manufactured as described above, the pore distribution is measured in the same manner as in the first embodiment, and the presence or absence of a peak in the region above 50 nm and below 200 nm and its height (dV / d(logD)) are measured. Then, the initial activity and durability evaluation tests are performed on the PtCo catalysts of Example 5 and Comparative Example 2. The method and conditions of the evaluation test are the same as those of the first embodiment, and the initial activity and the activity after degradation (after a total of 25,200 cycles in pretreatment to formal treatment) are evaluated by mass activity. The results of this characteristic evaluation and the initial activity test and durability test are shown in Table 3.

[0100]

[0101] As shown in Table 3, the catalyst of Example 5 having a barrier layer formed therein has a higher activity maintenance rate after the degradation test than the catalyst of Comparative Example 2 having no barrier layer. Therefore, it was confirmed that the use of a barrier layer is also useful in a catalyst whose catalyst particles are made of a platinum alloy.

[0102] Industrial Applicability

[0103] According to the present invention, a good initial activity can be maintained as an electrode catalyst of a solid polymer fuel cell, and durability can be improved. The present invention contributes to the popularization of fuel cells and becomes the basis for solving environmental problems.

Claims

1. A catalyst for a solid polymer fuel cell, wherein catalyst particles containing Pt as an essential catalyst metal are supported on a carbon powder carrier, wherein: A barrier layer composed of a hydrophobic porous polymer is provided, which covers the carbon powder carrier and / or at least one of the catalyst particles.

2. The catalyst for a solid polymer fuel cell according to claim 1, wherein In the pore distribution curve based on the Log differential pore volume distribution, there is a peak in the region where the pore diameter is 50 nm or more and 200 nm or less.

3. The catalyst for a solid polymer fuel cell according to claim 1, wherein The height of the peak in the region where the pore diameter is 50 nm or more and 200 nm or less in the pore distribution curve based on the Log differential pore volume distribution is 1.0 or more.

4. The catalyst for a solid polymer fuel cell according to claim 1 or claim 2, wherein: The catalyst particles contain Pt and a metal M as a catalyst metal, and the metal M is at least any one of Co, Ni, Mn, Fe, Ti, Zr, and Sn.

5. The catalyst for a solid polymer fuel cell according to claim 1 or claim 2, wherein: The porous polymer forming the barrier layer is any one of polyvinyl acetate, polylactic acid, polymethyl methacrylate, polypropylene, polyvinyl chloride, polyethylene, polyacrylonitrile, polyvinyl alcohol, polyvinylidene fluoride, polyethylene imine and polystyrene.

6. The catalyst for a solid polymer fuel cell according to claim 1 or claim 2, wherein: The loading density of the catalyst particles is 30-70%.

7. A method for producing a catalyst for a solid polymer fuel cell, which is the method for producing a catalyst for a solid polymer fuel cell according to claim 1 or claim 2, comprising: A step of preparing a catalyst in which catalyst particles containing Pt as an essential catalyst metal are supported on a carbon powder carrier; a step of preparing a polymer solution in which a polymer is dissolved in a solvent; and After dispersing the catalyst in the polymer solution, the polymer solution is heated or cooled, or water is added to precipitate the polymer on the catalyst surface to form a barrier layer.

Citation Information

Patent Citations

  • Daigoeezokugenso mataha chitanno tankabutsusoto kuromuno tankabutsusono nijuhifukusoojusuru kobuzai

    JP1976052942A

  • Clutch device

    JP1985053223A

  • Electrode catalyst for fuel cell and its manufacturing method

    JP2010027364A

  • Catalyst for solid polymer electrolyte fuel cells and method for producing same

    WO2018194007A1

  • Catalyst for solid polymer fuel cells and method for producing same

    WO2019065443A1